Redesain Metode Role Playing dalam Optimalisasi Pembelajaran Keterampilan Berbicara pada Siswa SMA di Era Merdeka Belajar - Hardinata, Vanda; Warsiman; Abadi, Machrus (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
This research is intended to find an ideal formulation in learning speaking skills through redesigning the Role Playing method. This study uses a modified research and development (R&D) method. The results showed that redesigning the Role Playing method was effective in improving speaking skills. This effectiveness can be seen from the increase in learning outcomes in each implementation. The elements of accuracy in pronunciation, intonation, targeting accuracy, courage, fluency, loudness, gestures/mimics, diction/choice of words, and improvisation, in practice I obtained a percentage of 70.67%, in practice II 80.55%, and in practice III 89.81%. While the student response questionnaire shows a percentage of 74.69% of students giving a positive response. The conclusion is that redesigning the Role Playing method is effective for improving speaking skills, especially for high school (SMA) students.